2007
DOI: 10.1038/sj.ijo.0803767
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced cytokine responses and central adiposity in young women

Abstract: Background: Evidence suggests that people who are more responsive to psychological stress are at an increased risk of developing obesity. However, the biological mechanisms underlying this phenomenon are poorly understood. The cytokines leptin, interleukin-1 receptor antagonist (IL-1Ra) and interleukin-6 (IL-6) play a key role in fat metabolism and abnormal circulating levels of these proteins have been reported in obese people and in individuals subject to stress. Objective: This study investigated whether cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
3
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 50 publications
(75 reference statements)
4
50
3
3
Order By: Relevance
“…Previous studies have reported an association between early-life stress and obesity, and also a relationship between BMI and stress-induced cytokine response (Brydon et al 2008 ;Boynton-Jarrett et al 2010). Obesity itself is accompanied by low-grade inflammation, and adipocytes are a source of IL-6, CRP and serum amyloid A (SAA) (Kvasnicka et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported an association between early-life stress and obesity, and also a relationship between BMI and stress-induced cytokine response (Brydon et al 2008 ;Boynton-Jarrett et al 2010). Obesity itself is accompanied by low-grade inflammation, and adipocytes are a source of IL-6, CRP and serum amyloid A (SAA) (Kvasnicka et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, young women with greater abdominal obesity had larger stress-induced inflammatory responses compared to those with less abdominal obesity [80]. Furthermore, obesity’s impact on reactivity appears to persist for subsequent stressors.…”
Section: Biopsychosocial Risk Factors For Elevated Inflammationmentioning
confidence: 99%
“…Stress also increase cytokine response (86) especially in abdominal obese subjects (87). Insulin resistance is characterized by low-grade inflammation and adipokines such M a n u s c r i p t 15 as TNFalpha decrease both insulin signalling, glucose uptake (88) and capillary recruitment (89).…”
Section: Neuroendocrine Effects On Endothelial Function and Muscle Glmentioning
confidence: 99%